2018
DOI: 10.15324/kjcls.2018.50.2.85
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Antibiotic Resistance Pattern ofStaphylococcus aureusIsolated by Clinical Specimens in a University Hospital in South Korea

Abstract: Information on the prevalence of S. aureus and the current antimicrobial resistance profile is necessary in selecting the appropriate treatment of S. aureus infections in any part of the world. This study examined the frequency and antibiotic resistance list of S. aureus isolates obtained from clinical specimens at one hospital in Korea. A total of 1,746 gram positive cocci collected were identified as S. aureus. S. aureus isolates were obtained from different samples including sputum (N=565; 32.4%), endotrach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…31 Multidrug resistant bacteria are di cult to treat and treatment results are less effective than for susceptible bacteria. 32 Multidrug resistance was found in 72.41% of isolates in this study, principally to penicillin, erythromycin and azithromycin. In the same way, in a study of healthcare workers in a children's hospital in Iran, found high levels of resistance to these drugs.…”
Section: Discussionmentioning
confidence: 63%
“…31 Multidrug resistant bacteria are di cult to treat and treatment results are less effective than for susceptible bacteria. 32 Multidrug resistance was found in 72.41% of isolates in this study, principally to penicillin, erythromycin and azithromycin. In the same way, in a study of healthcare workers in a children's hospital in Iran, found high levels of resistance to these drugs.…”
Section: Discussionmentioning
confidence: 63%